Materials and technologies for soft implantable neuroprostheses - Lacour, Stephanie P.; Courtine, Gregoire; Guck, Jochen (Nature Reviews Materials, 2016)
Implantable neuroprostheses are engineered systems designed to restore or substitute function for individuals with neurological deficits or disabilities. These systems involve at least one uni- or bidirectional interface between a living neural tissue and a synthetic structure, through which information in the form of electrons, ions or photons flows. Despite a few notable exceptions, the clinical dissemination of implantable neuroprostheses remains limited, because many implants display inconsistent long-term stability and performance, and are ultimately rejected by the body. Intensive research is currently being conducted to untangle the complex interplay of failure mechanisms. In this Review, we emphasize the importance of minimizing the physical and mechanical mismatch between neural tissues and implantable interfaces. We explore possible materials solutions to design and manufacture neurointegrated prostheses, and outline their immense therapeutic potential.
CRIS-Team Scopus Importer:2022-08-05